The Student International Community of Practice: a critical reflection on the shared experience of being a member, using creative hermeneutics. (13th May 2020) - Sanders, Kate; Marriott-Statham, Kelly; Mackay, Maria; McMillan, Ailsa; Rennie, Karen; Robinson, Betty Ann; Teeling, Seán Paul
No abstract available